The realpolitik of nuclear risk: When political expediency trumps technical democracy - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2016)
In recent years, a growing number of researchers in science and technology studies have begun to examine the relationship between science and politics. Specifically, they focus on citizen participation in highly technical policy problems and explore the possibility of a technical democracy that avoids pitfalls of technocracy. This focus, however, downplays a possibly more serious obstacle to technical democracy than technocracy, namely, realpolitik. Based on ethnographic and textual data on citizen–government interactions in the aftermath of the Fukushima Daiichi Nuclear Disaster, we first show how citizens mobilised radiation detectors and counter-experts to force the Japanese government to admit scientific uncertainty about the permissible dose limit. We then explain why this successful mobilisation nonetheless had only a small impact on evacuation and compensation policies in terms of the pre-disaster structure of Japanese politics: the dominance of commission-based policy-making allowed the bureaucratic government to play realpolitik in the face of scientific uncertainty to expediently purse its own interest, circumventing both democratic deliberation and technical rigour.